IMPLEMENTASI KERJASAMA DIREKTORAT JENDERAL IMIGRASI DAN LEMBAGA PERBATASAN DI INDONESIA - Angga Maulana Adha Sitorus; Arif Satria Hunianto; Syarif Hidayatullah (Universitas Labuhanbatu, 2023)
The Directorate General of Immigration is an example for other agencies in terms of developing innovations or other things that are able to increase the effectiveness of public services in Indonesia.Â One of them is the cooperation between the Directorate General of Immigration and several border institutions in Indonesia. Institutions that are in direct contact with the border between Indonesia and other existing countries such as Customs and the National Border Agency of the State. The establishment of the Cooperation is to overcome the abuse of authority by foreigners in Indonesia such as the smuggling of illegal goods, humans or even the existence of terrorism associations. With the existing cooperation, it is hoped that it can be a preventive step for possible violations that occur. In this study, it will be discussed about the implementation of the Cooperation and what future innovations can be done to improve existing cooperation. Â This research uses normative research methods with an approach that is carried out on the basis of materials to study theoretical problems related to concepts, views, principles, legal doctrines, legal rules and systems. So as to conclude that the implementation of existing cooperation between the Directorate General of Immigration and Border Institutions in Indonesia is effective or notKeywords : Directorate General of Immigration, Borders, Cooperation